2012
DOI: 10.1080/01411926.2011.613453
|View full text |Cite
|
Sign up to set email alerts
|

Measuring students’ transition into university and its association with learning outcomes

Abstract: Previously we showed how we measured pedagogy and revealed its association with learning outcomes of sixth-form college mathematics students. In this project we followed a similar approach to the study of university transition. We particularly sought to identify the students' perceptions of the transitional experience, and measure the association with learning outcomes. We drew on longitudinal surveys of students entering different programmes in five universities. Following them into their first year or so, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…However, studies involving several possible predictive factors are scarce. One exception is the study by Pampaka, Williams and Hutcheson [13] which is a mixed-method study, including a quantitative measurement of students' transitional experience, similar in spirit to the study reported on in the present paper. They reported that students' perceptions of the transition to university mathematics, their degree of positivity towards the transition and their self-efficacy are good predictors for the development of positive dispositions to university studies in mathematics.…”
Section: Introductionmentioning
confidence: 93%
“…However, studies involving several possible predictive factors are scarce. One exception is the study by Pampaka, Williams and Hutcheson [13] which is a mixed-method study, including a quantitative measurement of students' transitional experience, similar in spirit to the study reported on in the present paper. They reported that students' perceptions of the transition to university mathematics, their degree of positivity towards the transition and their self-efficacy are good predictors for the development of positive dispositions to university studies in mathematics.…”
Section: Introductionmentioning
confidence: 93%
“…The number of participants in the survey and the number of interviewees decreased as the project progressed due to student attrition (for example, students changing programmes or leaving the universities). For a quantitative analysis of the survey data, please refer to [3]. An interesting anecdote: we found some reluctance from engineering departments to contact their upcoming students with a survey about mathematics, as there was concern that the idea they would have to study mathematics might put them off coming.…”
Section: Introductionmentioning
confidence: 99%
“…La transición a la Universidad es un proceso complejo, multifactorial que requiere del estudiante significativos y múltiples cambios y adaptaciones, en un período que podemos estimar en dos años (Gall, T. L., Evans, D. R. y Bellerose, S., 2000; Pampaka, M., Williams, J., y Hutcheson, G., 2012;Pérez, C. L., 2015). Los y las estudiantes deberán generar no sólo nuevas maneras de pensar, también tendrá que crear relaciones sociales y culturales con sus profesores, compañeros y compañeras en un entorno desconocido.…”
Section: Contextounclassified